Penguatan Kompetensi Sdm Umkm Melalui Pelatihan Manajemen Sumber Daya Manusia Di Kecamatan Pasarwajo - Deki Pardana; Rusdin; Ahmad Daholu; Lalu Muh Abdul Wahid (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program aims to strengthen human resource management competencies among MSME owners, through structured training and mentoring activities. A participatory approach was implemented using a series of training sessions covering workforce planning, employee administration, recruitment procedures, job descriptions, performance evaluation, and reward and punishment systems. Practical discussions and mentoring enabled participants to apply HR management concepts directly to their businesses. The results demonstrated significant improvements in participants’ understand ing and ability to identify workforce requirements, prepare employee administrative documents, develop clear job descriptions, establish written employment agreements, and implement fair performance appraisal mechanisms. Participants also showed greater awareness of professional HR practices that support employee motivation and organizational effectiveness. Overall, the program successfully trans formed informal human resource management practices into more structured, systematic, and sustainable approaches, thereby enhancing the managerial capacity and long-term competitiveness of local MSMEs.